The Influence of External Audit Quality on Discretionary Accruals and Real Earnings Management Practices: An Analysis of Malaysian Firms - Muhammad Shaheer Nuhu,; Zauwiyah Ahmad,; Ying Zhee Lim, (Asian Academy of Management Journal, 2024)
This paper aims to analyse the mitigating effects of external audit quality (EAQ) factors on earnings management (EM) practices. Data were collected from firms listed on Bursa Malaysia’s main market, covering the years 2011 through 2022. Panel regression was employed to analyse the data. The findings of this study confirmed a significant negative association between audit reputation, audit quality, audit opinions, and EM of listed firms in Malaysia. Audit fees and audit tenure were found to be not significant in relation to EM. The study included five control variables in the analysis, and only economic value added (EVA) was found to be significant. The findings suggest that a number of audit quality factors are indicative of EM among listed firms. The authors extend, as well as contribute to, the growing literature on the EAQ, and therefore, wider corporate governance literature. Thus, it provides originality by presenting empirical evidence and outcomes to fully understand how discretionary accrual and real EM affect EAQ in the Malaysian context. Therefore, stakeholders should place higher concern on the selection of an external auditor, and investors should take into account the external audit factors when making investment decisions. Measuring the effectiveness of EAQ allows decision-makers to evaluate how effective employed governance measures are in improving shareholders’ perceptions of financial information quality and mitigating EM practices.